Modulation of Tissue Microenvironment Following Myocardial Infarction. Issue 8 (29th May 2022) - Handley, Ella‐Louise; Callanan, Anthony
Abstract : Significant progress has been made in methods for cardiac repair and regeneration within the past few decades; however, the diseased microenvironment of the infarct remains a limitation in the efficacy of therapies. A breadth of research is currently aiming to reverse this environment, focusing on immunomodulation, scavenging of oxidative species, and increasing oxygen levels within the tissue, either directly using materials or oxygen therapy or secondarily via angiogenesis and neovascularization techniques. Herein, an overview of the current methods for reversal of infarcted cardiac tissue to a less‐diseased state, via biomaterials such as electrospun scaffolds, gels or nanoparticles, stem cells, and derived exosomes, drugs, or bioactive molecules such as growth factors, is provided. Often, combinations of therapies are complementary and induce a superior response. Finally, a brief summation of recent clinical trials is provided. Abstract : Following myocardial infarction, the diseased microenvironment of the infarct minimizes the efficacy of regenerative therapies. The current review article examines the methods to regulate infarcted cardiac tissue, from biomaterials to stem cells to drugs, highlighting the synergistic effect of applying multiple therapies and investigating current clinical treatments.